Susceptibility of the poultry strain Musca domestica Linnaeus (Diptera: Muscidae) larvae toward pyrethroids and organophosphate insecticides - Kalaavathi Manoharani; Nurulhusna Abdul Hamid; Siti Nasuha Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Musca domestica Linnaeus is well-known as a pest that mechanically spreads diseases that are both medical and veterinary importance. Resistance has developed in the field as a result of the prolonged and improper application of insecticides to control the number of houseflies. The purpose of this study was to investigate the resistance status of poultry strain M. domestica larvae towards pyrethroid insecticides namely permethrin and deltamethrin, as well as organophosphate insecticides namely malathion and temephos. The third instar of susceptible poultry strains of M. domestica larvae was subjected to topical insecticide bioassay with concentrations ranging from 0.0005mg/L to 2000.0mg/L. The resistance ratio was calculated to categorize the level of resistance by dividing the LC 50 value of the poultry strain by the susceptible strain. The susceptibility status of the poultry strains, Sungai Lembu (SL) and Tapah Road (TR) towards pyrethroid and organophosphate revealed moderate to high resistance in comparison to the susceptible IMR strain (13.78-fold to 48.82-fold). Both strains were found to be resistant and possess multiple resistance and cross-resistance towards the tested insecticide. Understanding the resistance status of targeted pests is critical for effective, economically feasible, and environmentally sustainable pest management strategies in agriculture and beyond. It contributes to food security, environmental protection, and long-term pest control efficacy. Additionally, it is advisable to implement integrated pest management strategies and utilize synergists to enhance the effectiveness of both chemical based insecticides and biopesticides.